Flares in the changing look AGN Mrk 590 – I. The UV response to X-ray outbursts suggests a more complex reprocessing geometry than a standard disc. Issue 3 (2nd December 2022) - Lawther, D; Vestergaard, M; Raimundo, S; Koay, J Y; Peterson, B M; Fan, X; Grupe, D; Mathur, S
ABSTRACT: Mrk 590 is a known changing-look active galactic nuclei (AGNs) which almost turned off in 2012, and then in 2017 partially re-ignited into a repeat flaring state, unusual for an AGN. Our Swift observations since 2013 allow us to characterize the accretion-generated emission and its reprocessing in the central engine of a changing-look AGN. The X-ray and UV variability amplitudes are higher than those typically observed in 'steady-state' AGN at similar moderate accretion rates; instead, the variability is similar to that of highly accreting AGN. The unusually strong X-ray to UV correlation suggests that the UV-emitting region is directly illuminated by X-ray outbursts. We find evidence that the X-rays are reprocessed by two UV components, with the dominant one at ∼3 d and a faint additional reprocessor at near-zero lag. However, we exclude a significant contribution from diffuse broad line region continuum, known to contribute for bonafide AGN. A near-zero lag is expected for a standard 'lamp-post' disc reprocessing model with a driving continuum source near the black hole. That the overall UV response is dominated by the ∼3-d lagged component suggests a complicated reprocessing geometry, with most of the UV continuum not produced in a compact disc, as also found in recent studies of NGC 5548 and NGC 4151. None the less, the observed flares display characteristic time-scales of ∼100 rest-frame days, consistent with the expected thermal time-scale in an accretion disc.